Ecological aspiration and the income of farmers aroused by Grain for Green Project - Chen, Shengdong; Duan, Pei; Yu, Xiaoying (Frontiers in Ecology and Evolution, 2022)
For farmers, the more fragile the state of the ecology becomes, the more their awareness of the need for environmental protection grows. China’s Grain for Green Project (G.G.P.) policy of returning farmland to forests and grassland, as an external shock to the environment, has sparked people’s ecological aspirations. Many people have noticed the phenomenon of ecosystem degradation and overlapping poverty. Analyzing the environmental and income changes brought about by the G.G.P., and this study considers farmers’ self-selection problems due to their lack of subjective thinking regarding this initiative. Our study aims to fill this gap by using a forest–grass model to assess the level of farmers’ ecological aspirations in ecologically vulnerable areas of Xinjiang, China. This article is based on aspiration theory and a theoretical model assessing the economic impact of ecological aspiration on the G.G.P. in China. The results show that farmers’ ecological aspirations can increase their enthusiasm to participate in the G.G.P. Under counterfactual conditions, participation in the G.G.P. initially reduces farmers’ total income to a certain extent; however, in the long run, it can significantly increase the total income of farmers. When the intermediary effect is used to analyze the economic effect of ecological aspiration on returning farmland to forest, it is found that farmers’ ecological aspirations affect household income by influencing income expectations. Our findings have essential practical implications and provide an important reference for consolidating poverty alleviation efforts and effectively promoting rural revitalization. In addition, the results suggest a way to achieve the goals of carbon peak and carbon neutrality, and it is necessary for building environmental-friendly regions.